XX International Congress of Zoology (26-29 August, 2008) - Zootaxa, Zootaxa (Zootaxa, 2007)
Held every four years, the International Congress of Zoology (ICZ) gives zoologists and professionals from all fields related to zoology the chance to come together to discuss the current status of zoology and to share ideas about future development of all its disciplines.